AUDITORÍA DE LA INFRAESTRUCTURA TECNOLÓGICA DE LA FÁBRICA QUICORNAC DEL CANTÓN VINCES - Anchundia Bustamante, Fátima De Lourdes (2018)
The Company Quicornac S.A. is a multinational company of Swiss origin-Ecuadorian dedicated to the production and commercialization of juices and concentrates of tropical fruits, this company has been in permanent evolution since it counts on more than 32 factories at national level and international markets, having its main factory in Vinces in Sucre and Herbert Freire streets, its headquarters in Guayaquil is located in the Conauto building, its address is Avenida Juan Tanca Marengo at km 1.8. The company established its first factory in the year of 1989, being in the year 1,990 its first functions with 25 workers, its specific point of production was the concentrate and juice of maracuyá for export, reaching a good reputation in the year 1.991 Due to its good export quality, the company was able to innovate its machinery now, with the right technology. The purpose of this study is to audit the technological infrastructure of the Quicornac SA factory. since at present it is looking for the development of new products and higher quality systems required by the standards of the control organisms, for this it is necessary to have a good security in the network system so that there is no leakage of information. We will use a methodology based on the international standard that manages information security in a company, which can be executed in companies with or without profit, whether large or small, companies can also be public or private, we are talking of the ISO 27001 standard and so we will also use good quality standards. In the Audit area, the evaluation begins with the physical part of a network, structured cabling conditions, maintenance of the server room, communication cabinets, cable labeling, order, cleaning.